Neutrophilic Inflammation in the Immune Responses of Chronic Obstructive Pulmonary Disease: Lessons from Animal Models - Gang Huang; Xu-Chen Xu; Jie-Sen Zhou; Zhou-Yang Li; Hai-Pin Chen; Yong Wang; Wen Li; Hua-Hao Shen; Zhi-Hua Chen (Journal of Immunology Research)
Chronic obstructive pulmonary disease (COPD) is a major cause of mortality worldwide, which is characterized by chronic bronchitis, destruction of small airways, and enlargement/disorganization of alveoli. It is generally accepted that the neutrophilic airway inflammation observed in the lungs of COPD patients is intrinsically linked to the tissue destruction and alveolar airspace enlargement, leading to disease progression. Animal models play an important role in studying the underlying mechanisms of COPD as they address questions involving integrated whole body responses. This review aims to summarize the current animal models of COPD, focusing on their advantages and disadvantages on immune responses and neutrophilic inflammation. Also, we propose a potential new animal model of COPD, which may mimic the most characteristics of human COPD pathogenesis, including persistent moderate-to-high levels of neutrophilic inflammation.